Liquidity and the Business Cycle - Randi Næs; Johannes A. Skjeltorp; Bernt Arne Ødegaard (Norges Bank, 2008)
We show evidence of a contemporaneous relation between stock market liquidity and the business cycle. Stock market liquidity worsen when the economy is slowing down, and this effect is most pronounced for small firms. Using data for both the US and Norway, we find strong evidence that stock market liquidity predict the current and future state of the economy. We also show some evidence that can shed light on the link between stock markets and the real economy. Using stock ownership data from Norway, we find that the portfolio compositions of investors change with the business cycle, and that investor participation is correlated with market liquidity, especially for the smallest firms. This suggest a "flight to quality" during economic downturns where traders desire to move away from equity investments in general, and within their equity portfolios, move from smaller/less liquid stocks to large/liquid stocks. Our results suggest that an important explanation for the equity premium in general, and the equity size premium in particular, may be related to time variation in stock market liquidity at business cycle frequencies.
hdl:11250/2497774
Keywords: G10; G20; 330; market microstructure; liquidity; business cycles